2016
DOI: 10.1111/adj.12409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of photodynamic therapy adjunct to scaling and root planing in periodontitis patients: A randomized clinical trial

Abstract: Within the limits of the study, PDT adjunct to scaling and root planing does not lead to quantitative reduction of Aa in periodontitis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 50 publications
0
30
0
4
Order By: Relevance
“…Torrungruang et al showed that bacterial prevalence and quantity were higher in severe periodontitis subjects compared than in no/mild periodontitis subjects [ 13 ]. Several clinical trials have also evaluated the effectiveness of periodontitis treatment through the quantification of bacteria by qPCR [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Torrungruang et al showed that bacterial prevalence and quantity were higher in severe periodontitis subjects compared than in no/mild periodontitis subjects [ 13 ]. Several clinical trials have also evaluated the effectiveness of periodontitis treatment through the quantification of bacteria by qPCR [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aggregatibacter actinomycetemcomitans -0 Fusobacterium nucleatum Although in our study the presence of A. actinomycetemcomitans was inconstant, there are other reports suggesting that conventional SRP alone is inefficient in eliminating aerobe facultative anaerobe species as A. actinomycetemcomitans and it is appropriate to combine other therapies with SRP to remove it from the periodontal pockets. [17][18][19] Based on this observation there is a possibility for the photoactivation of H 2 O 2 with 940 nm diode laser to eliminate aerobe and anaerobe species like A. actinomycetemcomitans and maybe others that could not be investigated in this study. Regarding the keystone periodontal bacteria from the red complex (P. gingivalis, T. denticola, and T. forsythia), all three groups showed high statistical results ( p = 0.000) at 1 month postoperative as given in Table 5.…”
Section: Discussionmentioning
confidence: 98%
“…3). Os trabalhos de Moreira et al (2015); Queiroz et al (2015) e Pulikkotil et al (2016) constataram também superioridade do grupo TF, mas diferentemente do presente estudo, obtiveram melhora nos dois grupos.…”
Section: Terapia Fotodinâmicaunclassified
“…Segundo Alwaeli et al (2015), Jervøe-Storm et al (2015), Moreira et al (2015), Queiroz et al (2015), Carrera et al (2016), Pulikkotil et al (2016), Vohra et al (2016) e Belinello-Souza et al (2017), a terapia fotodinâmica (TF) tem sido proposta como adjuvante no tratamento da doença periodontal pelo efeito antimicrobiano, com a vantagem de não causar resistência bacteriana (Jervøe-Storm et al, 2015;Vohra et al, 2016), mas sem estudos publicados desse emprego, em equinos.…”
Section: Introductionunclassified
See 1 more Smart Citation